Gamification : using game elements in serious contexts - Stieglitz, Stefan; Lattemann, Christoph, 1970-; Robra-Bissantz, Susanne; Zarnekow, Rüdiger; Brockmann, Tobias (Progress in IS., 2017)
This compendium introduces game theory and gamification to a number of different domains and describes their professional application in information systems. It explains how playful functions can be implemented in various contexts and highlights a range of concrete scenarios planned and developed for several large corporations. In its first part the book presents the fundamentals, concepts and theories of gamification. This is followed by separate application-oriented sections - each containing several cases - that focus on the use of gamification in customer management, innovation management, teaching and learning, mobile applications and as an element of virtual worlds. The book offers a valuable resource for readers looking for inspiration and guidance in finding a practical approach to gamification.